Arqueologia Tupiguarani: relações entre as implantações dos sítios e cultura material no Médio Rio Doce - Henrique Moreira Duarte Pilo (2008)
During the diagnosis, prospecting and archaeological rescue programs in the coverage area of the enterprise denominated Aimorés Hydroelectric power station, an important question emerged about the relationship between the places of settlement and the forms and functions of lito-ceramic material culture found. Despite the theme relevance, it was not exhausted during the studies, and is a question of great value in regard to the best knowledge of past occupations in the region. It is known that by morphological rebuilding,even if virtual, from some fragments, it is possible to establish the possible uses of ceramic utensils. Therefore, attempts were made in this dissertation to answer basically related questions on a relation, direct or indirect, of the space occupation forms, with settlements on tops or terraces, proximity to major drainage and Tupiguarani material culture, possibility of establishing an use of space pattern in the studied archaeological sites based on ceramic material found during the excavations and finally, from analysis of Neutron Activation of the ceramic fragments samples what would be the possibility of establishing relations between the raw material of tool and a possible network distribution of material culture in the region.